Qur’anic Words: An Analysis on Shihab’s Rules of Exegesis in Tafsir Al-Mishbah - Ahamad Ahmadi Sakat; Abur Hamdi Usman; Muhammad Masruri; Mohd Fauzi Mohd Amin; Mohd Nazri Ahmad; Muhd Najib Abdul Kadir (Richtmann Publishing Ltd, 2024)
Vol. 6 No. 4: Supplement 1, July 2015